Comment on "Giant dielectric response in (Nb + Zn) co-doped strontium titanate ceramics tailored by atmosphere". (August 2020) - Tkach, Alexander; Okhay, Olena
Abstract: With this contribution, as a comment to the publication in Scripta Materialia 170 (2019) 166, reporting giant dielectric response in (Nb + Zn) co-doped strontium titanate ceramics tailored by atmosphere, we show that the reported ceramics should not be called co-doped due to volatilization of Zn and therefore suggested mechanisms for the giant permittivity response are not valid or doubtful and have to be reconsidered. Some data analysis results are found to contradict that in the literature as well.